Species of Philorus Kellogg from China with description of a new species (Diptera: Blephariceridae) - Kang, Zehui; Yang, Ding (Zootaxa, 2012)
The genus Philorus is newly recorded from the Chinese mainland. One species, Philorus levanidovae Zwick, is recordedfrom China for the first time. Another species, Philorus emeishanensis sp. nov., is described as new to science. The genus Philorus is discussed and a key to the known species from China is presented.